On invariant measures of nonlinear Markov processes. (1993) - Ahmed Ahmed, N. U. N. U.; Ding Ding, Xinhong Xinhong
Abstract : We consider a nonlinear (in the sense of McKean) Markov process described by a stochastic differential equations in R d . We prove the existence and uniqueness of invariant measures of such process.